Laparoscopic evaluation of the small intestine in the standing horse: Technique and effects*. Issue 6 (29th April 2017) - Jones, Andrew R. E.; Ragle, Claude A.; Anderson, Dusty; Scott, Coryelle
Abstract: Objective: To evaluate the feasibility and clinical outcomes after laparoscopic evaluation of the small intestines via laparoscopy. Study Design: Prospective pilot study. Animals: Healthy adult horses (n = 5). Methods: Horses were restrained in standing stocks and received an infusion of detomidine. One port was placed in the left last intercostal space and 3 ports were placed in the right paralumbar fossa. The small intestine was run with atraumatic laparoscopic grasping forceps, from the duodenocolic plica to the ileocecal plica. Postoperative pain was scored every 4 hours for the first 48 hours. Horses were monitored via physical examinations for 2 weeks. Second look laparoscopy was repeated at 2 weeks, to run the small intestine and assess iatrogenic changes. An exploratory celiotomy was performed in 2 horses, 2 months later and long‐term follow‐up was recorded in 3 horses. Results: Laparoscopic evaluation of the entire small intestine was successfully completed twice in every horse. This evaluation lasted 39 ± 21.2 minutes (mean ± SD), while total surgery time was 73 ± 34.1 minutes. Postoperative physical examinations remained normal in all horses, and pain scores were scored as mild. The only abnormalities at second look laparoscopy consisted of multifocal petechiae and ecchymoses in all horses, resolved by 2 months in the 2 horses explored via celiotomy. Three horses with long‐term follow‐up were healthy 8 months after the study. Conclusion: Running the small intestine laparoscopically is a feasible procedure in standing normal horses, and does not cause significant discomfort nor complications.